Effect of an Education Intervention on Knowledge of Junk Foods, Healthy Food Habits Among the School-Going Children at Selected Schools In Chennai, India – A Pre-Experimental Multicentric Trial.: Life Sciences-Nursing - Mohanram, K. Mageswari; C, Helen Shaji J (International Journal of Life Science and Pharma Research, 2023)
Junk food has replaced healthy, nutritious food as a new slogan among school children because it is more tasty, convenient, less expensive, and easier to prepare. However, it has no nutritional value and contains unhealthy ingredients, which pose numerous health risks when consumed regularly. As a result, school children aged 6 to 12 are easily enticed and addicted to junk foods, impacting their growth, concentration, feelings, and behavior. Education intervention regarding common junk foods and their health hazards, as well as methods to promote healthy eating habits, will aid in improving the nutritional status of young minds and curbing junk food addiction. One shot single test pre-experimental design was used to conduct the study among 120 school children at selected schools in Chennai, India, by non-probability homogenous purposive sampling method. Demographic proforma and self-structured questionnaires were used to collect the data from the children. The knowledge was classified into satisfactory(adequate), moderate and inadequate. The education intervention was given to all the students via a structured audio-visual aid. This intervention was given in three stages, and five experts validated the questionnaire. In the pre-test, 32.5% had inadequate knowledge, 67.5% had moderate knowledge, and none had adequate knowledge, but in the post-test, 95.5% of children had adequate knowledge of junk foods and their health hazards, with a significance at P<0.01. Based on the study results, the education intervention was very effective (P<0.01) in improving school children’s knowledge of junk foods, their health hazards, and the promotion of healthy food habits.